Maple syrup urine disease-treatment and outcome in patients of Turkish descent in Germany - Simon, Eva; Wendel, Udo; Schadewaldt, Peter (The Turkish Journal of Pediatrics, 2005)
Maple syrup urine disease (MSUD) is a rare autosomal recessive disorder that causes acute and chronic brain dysfunction because of a neurotoxic effect of the accumulating branched chain amino acids (BCAA) and their corresponding keto acids. Aim of the treatment is a rapid reversal of the neonatal decompensation and a stable long-term metabolic control obtained by a carefully adjusted BCAA-low diet. In optimally treated patients, an unimpaired neurological and intellectual outcome is possible. Ten patients of Turkish origin suffering from MSUD are presently treated in the Metabolic Unit of the University Hospital in Düsseldorf, Germany. All patients show mild intellectual deficits; neurological impairment is rare. This paper aims to define the feasible standard of therapy and the resulting intellectual and psychosocial outcome achievable in MSUD patients of Turkish origin under high standard conditions of medical care for inborn errors of metabolism.